VOLUMETRIC ANALYSIS OF THE OROPHARYNX ACCORDING TO CRANIOFACIAL MORPHOLOGY USING CBCT IN SEVENTH-CYCLE STUDENTS AT THE FACULTY OF DENTISTRY, UNIVERSITY OF CUENCA - Bravo Calderon, Manuel Estuardo; Lazo Santacruz, Lissbeth; Quizhpi Zatisaval, Geovanny Matias; Ojeda, Edisson; Soto Santiana, Anderson Steve (RECISATEC - REVISTA CIENTÍFICA SAÚDE E TECNOLOGIA - ISSN 2763-8405, 2024)
To perform a volumetric analysis of the oropharynx using cone beam computed tomography in seventh-cycle dental students with diverse facial biotypes and skeletal patterns. Methods: The tomographic sample was obtained from a group of 34 seventh cycle students of the Faculty of Dentistry, whose age range is 20 to 30 years. The tomographic samples were obtained through an imaging center in the city of Cuenca. Results: There was no significant difference between oropharyngeal volume and facial biotype, and there was no difference between oropharyngeal volume and skeletal pattern. The results obtained were that the lowest volume was in skeletal class II and in the mesofacial biotype and, on the contrary, a greater volume was found in class I and in the brachyfacial biotype. Conclusions: CBCT is nowadays an imaging method of great importance within the dental field, in which the study allowed us to identify that there is no significant difference in oropharyngeal volume with respect to facial biotype and that, in terms of skeletal class, a slight increase or reduction can be observed.